The gravimetric coefficient of indexes of integral estimation of readiness of future officers to the management physical preparation - Ol'khoviy O.M (Kharkov National Pedagogical University, 2012)
A purpose of work is determination of degree of importance and priority of indexes of integral estimation of readiness of graduating student to guidance, organization and leadthrough of physical preparation in subdivision. Combination of elements of the expert questioning is utillized on the method of Del'fi and method of modern theory of the hierarchical systems of T.Saati. The author automated informative system is created. The system is intended for collection, quantitative comparison of measure of advantage of one constituent above other and treatment of results of expert estimation. The coefficients of ponderability are certain practical (0,184), cognitive (0,113), personality (0,438) and activity (0,265) indexes of integral estimation of readiness of students to the management physical preparation. Possibilities of correction of model of preparation of future officers are rotined to the management in subdivisions of military powers and executable code of educational discipline "Physical education, special physical preparation and sport".